Pengaruh Trend FOMO (Fear Of Missing Out ), Konten Marketing Dan Flash Sale Terhadap Minat Beli Pada Tiktok Shop - Sale Sundava; Ezizwita (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to determine the Effect of FOMO (Fear Of Missing Out) Trend, Marketing Content and Flash Sale on Purchase Interest in Tiktok Shop. The population in this study were 946 FEB students at Dharma Andalas University, Padang, with sampling using a Raosoft sample size calculator, resulting in a sample of 121 respondents. Data were obtained by distributing questionnaires, then processed and tested using IBM SPSS Statistics 22. From the research conducted, it is known that based on the results of hypothesis testing, 1). FOMO (Fear Of Missing Out) Trend has a significant effect on Purchase Interest, 2). Marketing Content has a significant effect on Purchase Interest, 3). Flash Sale has a significant effect on Purchase Interest, 4) FOMO (Fear Of Missing Out) Trend, Marketing Content and Flash Sale have a significant effect on Purchase Interest. Furthermore, the Purchase Interest variable is influenced by the FOMO (Fear Of Missing Out) Trend, Marketing Content and Flash Sale by 76%, while the remaining 24% is influenced by other variables not included in this study, namely Purchase Decisions, Discounts, Tiktok Affiliates and Live Streaming.